Meta-Analysis of Lymphocytes in Schizophrenia: Clinical Status and Antipsychotic Effects - Miller, Brian J. (2012)
BACKGROUND: Schizophrenia is associated with immune system dysfunction, including abnormal blood immune cell parameters. We performed a meta-analysis of these associations, considering the effect of clinical status and antipsychotic treatment following an acute exacerbation of psychosis. METHODS: We identified articles by searching Pub Med, PsychInfo, and ISI, and the reference lists of identified studies. RESULTS: Sixteen studies of blood lymphocytes met the inclusion criteria. There was insufficient data for a meta-analysis of the mononuclear phagocytic system. In cross-sectional studies, there was a significant increase in the CD4% and CD56% in acutely relapsed inpatients (AR). Absolute levels of total lymphocytes, CD3, and CD4, and the CD4/CD8 ratio were significantly increased, and the CD3% was significantly decreased in drug-native first-episode psychosis (FEP). In longitudinal studies, the CD4/CD8 ratio appeared to be state-related markers, as it decreased following antipsychotic treatment for acute exacerbations of psychosis. Absolute CD56 levels appeared to be a trait marker, as levels significantly increased following antipsychotic treatment for relapse. DISCUSSION: Blood lymphocyte abnormalities in drug-naïve FEP suggest an effect that may be independent of antipsychotic medications. While some parameters (CD4/CD8) may be state markers for acute exacerbations of psychosis, others (CD56) may be trait markers, however more longitudinal studies are needed. Although these findings could provide the basis for future hypothesis testing, a relatively small number of studies and subjects, lack of correlative data with clinical features, and inadequate consideration of potential confounding factors limit the results.